Nontrivial intensity correlation from a coherent continuous-wave laser beam - Joshi, Binod; Smith, Thomas A.; Shih, Yanhua (American Physical Society, 2024)
We report an experimental observation of nontrivial intensity correlation of a continuous-wave fiber ring laser. The laser beam consists of approximately 450 000 independent longitudinal cavity modes, each in a coherent state representing a group of identical photons. Based on Glauber's second-order coherence theory, we conclude that the nontrivial intensity correlation is the result of a randomly created and randomly paired distinguishable group of identical photons interfering with the pair itself. This result is fundamentally interesting and practically useful.